Future Perspectives and New “Frontiers” in Cardiac Rhythmology - Anselmino, Matteo; De Ferrari, Gaetano Maria (Frontiers in Cardiovascular Medicine, 2020)
In the last three decades the Cardiac Rhythmology field has experienced tremendous change and evolution. Our understanding of the underlying mechanism of arrhythmic diseases has dramatically improved, starting from the genetic and molecular mechanisms. Innovative pharmacological, and non-pharmacological treatment options have been introduced and arrhythmias previously considered “untreatable” are now successfully managed in most referral centres. The increasing awareness of the detrimental effects of arrhythmias on any underlying cardiac substrate, targeted as a potentially modifiable cause, has therefore led to an increasingly stronger effort in developing novel methods and approaches to treat the arrhythmia and improve patient’s health and quality of life. Of all potentially significant developments in the field, we have decided to focus on the approaches generally applicable to multiple arrhythmic cardiac disorders and related to the advancement of technology. More specifically, we will deal with electroanatomical mapping and lesion creation during interventional procedures.